Developing Interactive E-LKPD with Wizer.Me: A Needs Analysis for Enhancing Poetry Writing Skills in Junior High School Students in Palembang - Muhammad Edwin; Zahra Alwi; Izzah Izzah (AL-ISHLAH: Jurnal Pendidikan, 2025)
Writing skills are crucial in Indonesian language learning at the secondary school level. However, students’ creative writing abilities remain weak, and low motivation is often cited as a contributing factor. Therefore, an effective solution is needed to support creative writing instruction. This study aimed to analyze students' needs for an Electronic Learner Worksheet (E-LKPD) to enhance creative writing skills in junior high school. A survey method was employed, involving 294 students. Data were collected through questionnaires and interviews, and analyzed using both qualitative and quantitative techniques. The findings revealed three main points: (1) the E-LKPD should align with established principles of E-LKPD development, its characteristic features, and the fundamentals of poetry writing instruction; (2) existing E-LKPD exhibit significant shortcomings; and (3) teachers at Junior High School 56 Palembang express a strong need for interactive E-LKPD to support poetry writing instruction. The study underscores the necessity of developing more effective and engaging E-LKPD to improve students’ creative writing skills and overall literacy. Enhancing the quality of instructional materials could better motivate students and foster greater achievement in writing.